Industrial eco-productivity tool: A case study of industrial SMEs - Idoia Urain; Daniel Justel; Joan Manuel F. Mendoza; José Alberto Eguren (International Journal of Production Management and Engineering, 2023)
This paper presents a new, unified method to measure and increase production and environmental performance in industrial SMEs (Small and Medium Enterprises), which have very limited resources, by identifying areas to improve and forming related projects. This structured, easy-to-apply method is based on standard systems to measure waste production efficiency and eco-efficiency and unifies them in a single reference value. In addition, a case study is shown where the industrial eco-efficiency of the company is obtained with the developed tool.